A STUDY ON SELECTED PHYSIOLOGICAL VARIABLES OF HANDBALL, VOLLEYBALL AND FOOTBALL PLAYERS. - Babu, Mr.P.Madhusudhana (The journal of contemporary issues in business and government, 2013)
Sports and games in modern times have taken a definite shape in comparison with the immature and unscientific plays of ancient times. Today sports are becoming professional players are earning a lot through games and sports. Sports in recent times are mainly of a competitive nature through their procreative values cannot be underestimated or denied. Despite the fighting attitude between the competitors, sports bring the different nations closer and establish brotherhood and friendship between the people of different countries.